Challenges and Prospects for Women Entrepreneurs in Tunisia (Global Journal of Management and Business Research, 2023)
Summary- Women who do not have a salaried employment contract have the opportunity to work on a self-employed basis to generate an income Under self-employed status these women take on alone or perhaps in partnership all the financial administrative and social risks involved in developing their activities In this approach we will focus on the reality of these women who are self-employed The aim of this research is to understand the entrepreneurial process of women by distinguishing three different realities women entrepreneurs women in the professions and women involved in cooperatives This shows how complex and diverse the notion of female entrepreneurship is Through this research we defend the idea that we need to approach the situation of these women entrepreneurs from a systemic angle since their daily lives are the result of an interaction between their professional lives and their family lives